A simple method for differentiation of raw meat from various meat animals : Potential technique for detection of meat adulteration - RASOOL, T J; RAO, K B C APPA; BHAT, P P; RAWAT, A K; BHAT, P N (The Indian Journal of Animal Sciences, 2013)
The present study was undertaken to develop a simple method for the identification of raw meat obtained from various species, based on repetitive DNA sequences. Genomic DNA was isolated from miscle tissues of cattle, buffalo, sheep and goats and subjected to Eco RI and Pst I restriction enzyme digestion analysis. The genome of these closely related species of the family Bovidae contained spedel-specific repetitive DNA sequences. Eco Rl digestion revealed 1.4 and 0.7 kb fragments specific to cattle, 1.65 and 1.45 kb fragments specific to buffalo, 0.42 and 0,35 kb hands specific to sheep and 0.6 kb fragment specific to goat genomes. In contrast, Pst I digestion gave rise to a few variable repetitive bands which are feeble to identify as species specific, apan from their uniform monomorphic pattern. The results apparently demonstrated that raw meat derived from livestock animals of the family Bovidae can he identified using restriction enzyme analysis. Thus, the preliminary data suggested that the method seems to be simple and easy to perform for differentiation of meat of these closely related species.